PENGARUH KEGIATAN KHITOBAH TERHADAP PENINGKATAN KEPERCAYAAN DIRI SANTRI DI PONDOK PESANTREN SUNAN BONANG MOJOJEJER - Nur Ahyat; Mohammad Fahrudi Noer; Fitri Noviana Islamiyah (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Abstract The purpose of this research is to find out whether there is an influence sermon activities to increase students' self-confidence. Trust Self is something that is very important for every individual to have. With confidence we can face a difficult situation with easy. Khitobah activities are activities that focus on appearances in public or also known as speeches (public speaking). This research uses descriptive quantitative research methods using a questionnaire instrument in the form of a questionnaire. The questionnaire includes two indicators, namely sermon activities and self-confidence. Data analysis techniques used is a descriptive percentage formula using a product analysis test moment using SPSS, the results obtained are: based on the calculation results between variable X and the influence of the sermon activity on variable Y Student self-confidence is calculated using the product moment correlation formula then the result obtained is rxy = 0.593 while the significance level is 5% 0.266, so the result is a smaller coefficient, namely 0.593 > 0.266 so the result is that Ha is accepted and H0 is rejected. This means that There is a significant influence between sermon activities and self-confidence students at the Sunan Bonang Mojojejer Islamic boarding school